1992
DOI: 10.1089/jwh.1992.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Injury Patterns in High School Varsity Basketball

Abstract: An analysis of 2 years of injury surveillance data on female and male high school varsity basketball players gathered by certified athletic trainers at 196 schools around the nation is presented. In contrast to previous reports, the rate of sport-related injury (game and practice combined) was approximately the same for both sexes. The girls had a slightly higher proportion of moderate and major injuries than had the boys. Sprains were the most frequent type of injury for both sexes, and the most frequently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 9 publications
0
18
0
3
Order By: Relevance
“…ries requiring surgery. 12,13 In the United States, 20 000 to 80 000 high school female athletes experience anterior cruciate ligament (ACL) injuries each year, with most in soccer and basketball. 8,14,15 Long-term studies [16][17][18][19][20][21][22][23] show that despite treatment, knee and ankle injuries increase the risk of premature osteoarthritis.…”
mentioning
confidence: 99%
“…ries requiring surgery. 12,13 In the United States, 20 000 to 80 000 high school female athletes experience anterior cruciate ligament (ACL) injuries each year, with most in soccer and basketball. 8,14,15 Long-term studies [16][17][18][19][20][21][22][23] show that despite treatment, knee and ankle injuries increase the risk of premature osteoarthritis.…”
mentioning
confidence: 99%
“…Only three studies reported knee injury mechanisms (16%). The most common injury mechanisms were landing from a jump, shooting, guarding, and collision with another player 3 18 25. The type of treatment provided was reported in seven of the studies reviewed, although four of these studies provided information only on surgical interventions 17 20 22 23…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies have mainly focused on active populations such as high school, college, and professional athletes or military personnel. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Few studies have assessed sports-related injuries among general adult populations. 2,4,5,[21][22][23][24] Among sports and recreation-related injuries in the United States, those associated with basketball are one of the most common sports injuries that require medical treatment.…”
Section: Introductionmentioning
confidence: 99%